A lipase-responsive antifungal nanoplatform for synergistic photodynamic/photothermal/pharmaco-therapy of azole-resistant Candida albicans infections. Issue 100 (2nd December 2019) - Yang, Dongliang; Lv, Xinyi; Xue, Lei; Yang, Nan; Hu, Yanling; Weng, Lixing; Fu, Nina; Wang, Lianhui; Dong, Xiaochen
Abstract : A lipase-triggered drug release nanoplatform was synthesized for synergistic photodynamic/photothermal/pharmaco-therapy of azole-resistant Candida albicans infections. Abstract : A lipase-triggered drug release nanoplatform (PGL-DPP–FLU NPs) for multi-modal antifungal therapy is developed. The lipases secreted by C. albicans can accelerate FLU release. The ROS and heat produced by PGL-DPP–FLU NPs make C. albicans more vulnerable to FLU, thereby PGL-DPP–FLU NPs exhibit high performance for combating azole-resistant C. albicans biofilms and wound infection.